# 1/2(3/5x-8)+7/4(2/5x+4)

x + 3

Step-by-step explanation:

Use the distributive property, then collect like terms

(1/2)(3/5 x) + (1/2)(-8) + (7/4)(2/5 x) + (7/4)(4)

3/10 x - 4 + 7/10 x + 7

x + 3

## Related Questions

A fisherman uses a spring scale to weigh a tilapia fish. He records the fish weight as a kilograms and notices that the spring stretches b centimeters. Which expression represents the spring constant (1 =9.8 )? A). 980ab B). 9.8ab C). 9.8ab D). 980ab

k =

Step-by-step explanation:

Fisherman noticed a stretch in the spring = 'b' centimetres

Weight of the fish = a kilograms

If force applied on a spring scale makes a stretch in the spring then Hook's law for the force applied is,

F = kΔx

Where k = spring constant

Δx = stretch in the spring

F = weight applied

F = mg

Here 'm' = mass of the fish

g = gravitational constant

F = a(9.8)

= 9.8a

Δx = b centimetres = 0.01b meters

Therefore, 9.8a = k(0.01b)

k =

k =

Therefore, spring constant of the spring will be determined by the expression, k =

Evaluate the expression 9x - 5 for the values of x given in the first column.Value of x Value of expression
5
4
129
6
7

Step-by-step explanation:

Expression : 9x - 5

To fill the table using the expression, you have to replace each value with x and solve the expression.

The answer is attached to the picture.

Step-by-step explanation:

To fill the table using the expression

you have to replace each value with x and solve the expression

A​ 0.8-liter bottle of Mexican wine costs 101 pesos. At that​price, how much would a​ half-gallon jug of the same wine cost in​dollars?

$12.18 Step-by-step explanation: Given: Cost of 0.8 liter bottle of Mexican wine = 101 pesos or cost of 1 liter bottle of Mexican wine = pesos Now, 1 Mexican pesos = 0.051 dollars thus, cost of 1 liter bottle of Mexican wine = dollars also, 1 gallon = 3.78541 Liter Thus, half gallon = = 1.892705 Liters therefore, cost of half gallon jug = dollars or cost of half gallon jug of wine =$12.18

Use the order of operations to simplify: 9 ÷ 3 + 4 × 6

27

Step-by-step explanation:

First is 9 / 3 which is 3 and then 4 x 6 which is 24 then 24 + 3  = 27

PEMDAS

4 × 6 is 24

9 ÷ 3 is 3

24  + 3 = 27

Step-by-step explanation:

The expression 2x(5x - 1) +(3x2 - 7x - 2) is simplified into the form ax 2+ bx + c.What are the values of the coefficients a,b,c?
a:
b:
C:

Step-by-step explanation:

2x (5x - 1) + (3x^2 - 7x - 2)

= 10x^2 - 2x + 3x^2 - 7x - 2

= 13x^2 - 9x - 2

a = 13

b = -9

c = 2

ABCD is a trapezoid.
What is the area of trapezoid?

Let h represent the height of the trapezoid, the perpendicular distance between AB and DC. Then the area of the trapezoid is
Area = (1/2)(AB + DC)·h
We are given a relationship between AB and DC, so we can write
Area = (1/2)(AB + AB/4)·h = (5/8)AB·h

The given dimensions let us determine the area of ∆BCE to be
Area ∆BCE = (1/2)(5 cm)(12 cm) = 30 cm²

The total area of the trapezoid is also the sum of the areas ...
Area = Area ∆BCE + Area ∆ABE + Area ∆DCE
Since AE = 1/3(AD), the perpendicular distance from E to AB will be h/3. The areas of the two smaller triangles can be computed as
Area ∆ABE = (1/2)(AB)·h/3 = (1/6)AB·h
Area ∆DCE = (1/2)(DC)·(2/3)h = (1/2)(AB/4)·(2/3)h = (1/12)AB·h

Putting all of the above into the equation for the total area of the trapezoid, we have
Area = (5/8)AB·h = 30 cm² + (1/6)AB·h + (1/12)AB·h
(5/8 -1/6 -1/12)AB·h = 30 cm²
AB·h = (30 cm²)/(3/8) = 80 cm²

Then the area of the trapezoid is
Area = (5/8)AB·h = (5/8)·80 cm² = 50 cm²